Poly(1, 6-heptadiyne)/NiFe2O4 composite as capacitor for miniaturized electronics. Issue 18 (11th December 2020) - Magisetty, RaviPrakash; N R, Hemanth; Shukla, Anuj; Shunmugam, Raja; Kandasubramanian, Balasubramanian
ABSTRACT: Impedance spectroscopy-based electrical measurements were conducted on different molecular weight (MW) Poly(1, 6-heptadiyne)s (PHDs) embedded PHD/NiFe2 O4 nanocomposites. Nanocomposites conductivity result demonstrated the conductivities of around 3.5 × 10 − 6 − 16 × 10 − 6 S C m − 1 (nanocomposite Root mean square (RMS) current is 12–15 times greater than DC current of PHDs at 27° C). Additionally, dielectric loss and capacitance characteristics suggested the nanocomposite (4500 MW PHD) device quality factor is 35.7 at 1 kHz, which is ~13.89 times superior than that of NiFe2 O4 alone sample, also 'Q' value for highest MW PHD nanocomposite is 50% enhanced than NiFe2 O4 . Moreover, the capacitance result suggested the 12400 MW PHD nanocomposite nearly frequency-independent capacitance (15–20pF) over a frequency range of 500 Hz–500 kHz. Abstract :